Association between Matrix Metallopeptidase 9 Polymorphism and Breast Cancer Risk - Felizi, Rogério Tadeu; Veiga, Melissa Gonzalez; Carelli Filho, Ivo; Souto, Ricardo Peres do; Fernandes, César Eduardo; Oliveira, Emerson (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective Epidemiological studies have shown evidence of the effect of genetic variations in the pathogenesis of breast cancer and have suggested a relationship of the disease with genetic polymorphisms. Matrix metallopeptidase 9 (MMP-9) is a collagenase responsible for the degradation of type IV collagen, the major component of the basement membrane, and other essential extra cellular matrix components, being involved in the tumor cell invasion and metastasis. Our objective was to evaluate the relationship between the MMP-9-1562 C/T polymorphism (rs 3918242) and the risk of developing breast cancer.Methods In this case-control study, the frequency of the MMP-9-1562 C/T polymorphism (rs 3918242) was determined in 148 women with breast cancer and 245 women without the disease. The DNA was extracted from plasma samples, and the gene was amplified by polymerase chain reaction (PCR); the presence of the polymorphism was determined using restriction enzymes.Results After adjusting for confounding variables, we found that the polymorphism was not associated with the occurrence of breast cancer (odds ratio [OR] = 1.159, 95% confidence interval [CI]: 0.6625–1.997, p = 0.5964). We also found no association with more advanced disease, the presence of hormone receptors, human epidermal growth factor receptor 2 (HER2) overexpression, or rate of tumor cell proliferation.Conclusion We did not observe a relationship between MMP-9–1562 C/T polymorphism (rs 3918242) and the occurrence of breast cancer.
Keywords: MMP-9 metalloproteinase; breast cancer; genetic polymorphism; genetics; single-nucleotide polymorphisms